Guidelines for integrating gender concerns in the development processes a manual for the Philippine Development Plan for Women implementation in Northern Mindanao. - Philippines. National Commission on the Role of Filipino Women; Philippines. National Economic and Development Authority. Region X. (Manila National Commission on the Role of Filipino Women, 1998)
A manual for spatial and socio-economic gender responsive planning, programming and monitoring in the government and private sectors.
Cover-title.
"This manual is a product of a one-year pilot testing project on the required processes and mechanisms for the Philippine Development Plan for Women in our effort to implement R.A. 7192 in Northern Mindanao (Region X). This is a joint project of the NEDA and the NCRFW"--Foreword.
Keywords: Philippine Development Plan for Women -- Handbooks, manuals, etc; Women in development -- Philippines -- Northern Mindanao -- Handbooks, manuals, etc; Regional planning -- Philippines -- Northern Mindanao -- Handbooks, manuals, etc; Northern Mindanao -- Economic policy -- Handbooks, manuals, etc; Northern Mindanao -- Social policy -- Handbooks, manuals, etc